2006
DOI: 10.1111/j.1365-2648.2006.03990.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical environmental stimuli that turn healthcare facilities into healing environments through psychologically mediated effects: systematic review

Abstract: Studies that manipulate several environmental stimuli simultaneously clearly support the general notion that the physical healthcare environment affects the well-being of patients. However, when scrutinizing the effects of specific environmental stimuli, conclusive evidence is still very limited and difficult to generalize. The field thus appears to be in urgent need of well-conducted, controlled clinical trials. At present, and on the basis of the available research, it would be premature to formulate evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
279
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(293 citation statements)
references
References 38 publications
4
279
0
10
Order By: Relevance
“…Physical environment is defined as ambient, architectural or interior design features that are purely stimulus objects (Dijkstra et al, 2006;Harris et al, 2002) and that characterize the healthcare settings. Swan et al (2003) found that patients recovering in appealing rooms rated their rooms significantly higher than did patients in typical rooms in the same hospital, and Leather et al (2003) found that a relocated (and redesigned) waiting area originated more positive environmental appraisals, and greater reported environmental satisfaction than the traditional waiting area before relocation.…”
Section: Introductionmentioning
confidence: 99%
“…Physical environment is defined as ambient, architectural or interior design features that are purely stimulus objects (Dijkstra et al, 2006;Harris et al, 2002) and that characterize the healthcare settings. Swan et al (2003) found that patients recovering in appealing rooms rated their rooms significantly higher than did patients in typical rooms in the same hospital, and Leather et al (2003) found that a relocated (and redesigned) waiting area originated more positive environmental appraisals, and greater reported environmental satisfaction than the traditional waiting area before relocation.…”
Section: Introductionmentioning
confidence: 99%
“…They need to spend more time on detection (Blake et al, 2008) and this issue effects the colour detection on them as well (Ho et al, 2001). Therefore, the visual effect of colour on elderlies is different to the other age group, which needs a comprehensive investigation accordingly (Dijkstra et al, 2006). Within the years a few studies investigates the visual impact of colours on elderlies.…”
Section: Elderly Visual Abilitymentioning
confidence: 99%
“…Dijkstra et al (2006) and Ulrich et al (2004) showed that the psychological effect of an environment could release stress and increase the feel of relaxation. Previous researchers classified the comparison of colour emotions.…”
Section: Cool Colours Against Warm Coloursmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even within the constraints of EBD there is still discussion and debate as to what actually constitutes evidence. For example Dijkstra et al (2006), Huisman et al (2012) and Salonen et al (2013) to name but a few, have been extremely strict as to what could be considered as 'evidence', and claim only scientific research derived through randomised controlled trials is permissible, whilst other scholars' definitions are much looser, for example Hamilton and Watkins (2009) specific context, what is perhaps of equal importance is how such evidence is used by designers; how it is mobilised in 'designerly ways' (see Cross, 2001 and later for further description) by those engaging in the creation of our healthcare built environments ,something which remains relatively under-researched. A better understanding of how evidence in its many forms is used by designers in practice, through both performancebased and prescriptive-based approaches, can in turn help optimise how new and emerging evidence is included within future design guidance.…”
Section: Introductionmentioning
confidence: 99%